Pengaturan Kecepatan Motor Induksi Tiga Fasa Berbasis Teknik Modulasi Carrier Based Pulse Width Modulation (CBPWM) dengan Kendali Kontroller Fuzzy Logic - Darwinata, Lalu Ishadi; Wiryajati, I Ketut; Citarsa, Ida Bagus Fery (TIN: Terapan Informatika Nusantara, 2024)
Along with increasing progress in the industrial world in Indonesia, the need for equipment used in the production of goods has also increased. One of the important equipment in an industry is a driving tool. The electric motor is a driving tool that has a big influence on the goods production system. Therefore, this paper discusses speed regulation of electric motors, especially 3-phase induction motors using Carrier Based Pulse Width Modulation (CBPWM) with Fuzzy Logic control which was carried out in Mataram. The speed response of the system will be improved with Fuzzy Logic Control (FLC). The results of the observations are compared with a system controlled by a PID controller. Simulation results with Simulink show that the Fuzzy Logic controller based on Carrier Based Pulse Width Modulation Control provides a better response than the PID controller. This is shown when there is an overshoot of 0%, a rise time of 0.5 seconds and a setting time of 1.5 seconds, whereas on the PID controller when there is an overshoot of 0.4%, a rise time of 0.7 seconds, and a setting time of 2.5 seconds, for a motor reference speed of 2 rad/second and load torque 0, 25, 50, 75, 100, 125, 150, 200 Nm. From the simulation results, it is proven that using a Fuzzy Logic controller based on Carrier Based Pulse Width Modulation Control, the speed response of a three-phase induction motor is better than using a PID controller.